Layer-by-layer assembled polyampholyte microgel films for simultaneous release of anionic and cationic molecules - Wang, Xu (Langmuir : the ACS journal of surfaces and colloids, 2010)
A facile layer-by-layer (LbL) assembly method for the fabrication of matrix films capable of coloading and simultaneous release of oppositely charged molecules has been established by using polyampholyte microgels as building blocks. Polyampholyte microgels (named PAH-D-CO(2)) containing amine and carbamate groups were LbL assembled with polyanion poly(sodium 4-styrenesulfonate) (PSS) to produce PAH-D-CO(2)/PSS multilayer films. The successful fabrication of PAH-D-CO(2)/PSS multilayer films was verified by quartz crystal microbalance measurements and cross-sectional scanning electron microscopy. Anionic methyl orange and cationic rhodamine 6G were coloaded into PAH-D-CO(2)/PSS multilayer films because of the electrostatic interaction of these dyes with amine and carbamate groups in the PAH-D-CO(2)/PSS microgel films. The abundance of amine and carbamate groups as well as the swelling capacity of PAH-D-CO(2) microgels guarantees the high loading capacity of the PAH-D-CO(2)/PSS multilayer films toward the anionic and cationic dyes. Methyl orange and rhodamine 6G were simultaneously released from PAH-D-CO(2)/PSS multilayer films when immersing the dye-loaded films into 0.9% normal saline. The releasing behaviors of the polyampholyte microgel films can be tailored by capping the PAH-D-CO(2)/PSS films with barrier layers. The polyampholyte microgel films of PAH-D-CO(2)/PSS are expected to be widely useful as matrixes for coloading oppositely charged functional guest materials such as drugs and even for their controlled release